An econometric appraisal of monetary indicators on Malaysian sectors. - Yusof, Z. (2009)
This study examines various measures of monetary indicators in the Malaysian sectoral activity during 1970:1 to 2008:3. It provides with some evidence on the dynamic of the monetary policy variables based on sectoral output data. Some of the variables may response differently across the sector. Failure to examine the sectoral effects can lead to incorrect inferences on the monetary variables particularly when they are the intermediate targets. On how the variables affect the economy has long been debated by economists. This study seeks to investigate the role of the money, interest rate, bank credit and exchange rate in Malaysian economic activity, namely agriculture, construction, manufacturing and services. The econometric appraisal of the monetary indicators is based on the Johansen-Juselius (1992) cointegration techniques,vector error correction model (VECM) and parsimonious error correction model (PECM).